A Synthetic Biology Perspective on the Bioengineering Tools for an Industrial Microalga: Euglena gracilis - Chen, Zhenfan; Zhu, Jiayi; Du, Ming; Chen, Zixi; Liu, Qiong; Zhu, Hui; Lei, Anping; Wang, Jiangxin (Frontiers in Bioengineering and Biotechnology, 2022)
Euglena is a genus of single-celled eukaryotes that show both plant- and animal-like characteristics. Euglena gracilis, a model species, is of great academic interest for studying endosymbiosis and chloroplast development. As an industrial species, E. gracilis is also of primary biotechnological and economic importance as high value-added food, medicine, and cosmetic and high-quality feedstock for jet-fuel production because of its cells containing many high-value products, such as vitamins, amino acids, pigments, unsaturated fatty acids, and carbohydrate paramylon, as metabolites. For more than half a century, E. gracilis has been used as an industrial biotechnology platform for fundamental biology research, mainly exploring relevant physiological and biochemical method studies. Although many researchers focused on genetic engineering tools for E. gracilis in recent years, little progress has been achieved because of the lack of high-quality genome information and efficient techniques for genetic operation. This article reviewed the progress of the genetic transformation of E. gracilis, including methods for the delivery of exogenous materials and other advanced biotechnological tools for E. gracilis, such as CRISPR and RNA interference. We hope to provide a reference to improve the research in functional genomics and synthetic biology of Euglena.